2019
DOI: 10.1016/j.neulet.2018.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Insights from molecular dynamics simulations to exploit new trends for the development of improved opioid drugs

Abstract: Having accidental deaths from opioid overdoses almost quadrupled over the past fifteen years, there is a strong need to develop new, non-addictive medications for chronic pain to stop one of the deadliest epidemics in American history. Given their potentially fewer on-target overdosing risks and other adverse effects compared to classical opioid drugs, attention has recently shifted to opioid allosteric modulators and G protein-biased opioid agonists as likely drug candidates to prevent and/or reverse opioid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…One of the explicit assumptions of this review is therefore that allosteric binding sites for adrenergic compounds exist on the extracellular side of the orthosteric opioid binding site (Figures 1-3) as imputed from the binding studies and enhancement documented above. Notably, Traynor's group [104-107], Filizola's group [108][109][110], and Matosiuk's group [111,112] have each studied small molecule, non-adrenergic allosteric enhancers of opioid receptors and, using molecular dynamics studies, also located allosteric binding to a site extracellular to the orthosteric site and often involving transmembrane-to-extracellular loop regions as illustrated in Figures 1-3. Additionally, Uprety et al [113] demonstrated the existence of a computationally, synthetically, and pharmacologically validated allosteric binding site in MOR and KOR that involves the same transmembrane 5-extracellular loop 2 region identified in adrenergic binding studies (above).…”
Section: Mechanisms Underlying Opioid-adrenergic Enhancementmentioning
confidence: 99%
“…One of the explicit assumptions of this review is therefore that allosteric binding sites for adrenergic compounds exist on the extracellular side of the orthosteric opioid binding site (Figures 1-3) as imputed from the binding studies and enhancement documented above. Notably, Traynor's group [104-107], Filizola's group [108][109][110], and Matosiuk's group [111,112] have each studied small molecule, non-adrenergic allosteric enhancers of opioid receptors and, using molecular dynamics studies, also located allosteric binding to a site extracellular to the orthosteric site and often involving transmembrane-to-extracellular loop regions as illustrated in Figures 1-3. Additionally, Uprety et al [113] demonstrated the existence of a computationally, synthetically, and pharmacologically validated allosteric binding site in MOR and KOR that involves the same transmembrane 5-extracellular loop 2 region identified in adrenergic binding studies (above).…”
Section: Mechanisms Underlying Opioid-adrenergic Enhancementmentioning
confidence: 99%
“…TRV250 178 , which currently finished phase I clinical trials, is a G protein-biased DOR agonist that preferentially activates the G protein pathway showing reduced hyperalgesia in rodent models. In these studies, TRV250 is developed for the treatment of acute migraine and was shown to have a quick absorption of 0.5 to 2 hours upon s.c. administration, which increased by up to 3 hours upon oral administration and by up to 6 hours in conjunction with a high-fat meal.…”
Section: Trv250mentioning
confidence: 99%
“…Optimization of allosteric modulators, however, remains challenging, in part due to a lack of experimental high-resolution structures of opioid receptors bound to such molecules. Classic pharmacological studies and molecular dynamics simulations have begun to fill this gap (34)(35)(36). Further characterization of allosteric sites will likely enable not only ways to potentiate opioidergic signaling, but also potential avenues for opioid antagonists effective in reversing the effect of exceptionally potent opioids such as carfentanil (37).…”
Section: Molecular Recognition Of Opioidsmentioning
confidence: 99%